Accelerating typhoid conjugate vaccine introduction: what can be learned from prior new vaccine introduction initiatives? - Jamka, LP; Simiyu, KW; Bentsi-Enchill, AD; Mwisongo, AJ; Matzger, H; Marfin, AA; Pollard, AJ; Neuzil, KM (Oxford University Press, 2019)
The health consequences of typhoid, including increasing prevalence of drug-resistant strains, can stress healthcare systems. While vaccination is one of the most successful and cost-effective health interventions, vaccine introduction can take years and require considerable effort. The Typhoid Vaccine Acceleration Consortium (TyVAC) employs an integrated, proactive approach to accelerate the introduction of a new typhoid conjugate vaccine to reduce the burden of typhoid in countries eligible for support from Gavi, the Vaccine Alliance. TyVAC and its partners are executing a plan, informed by prior successful vaccine introductions, and tailored to the nuances of typhoid disease and the typhoid conjugate vaccine. The iterative process detailed herein summarizes the strategy and experience gained from the first 2 years of the project.